Pengaruh Brand Image Terhadap Keputusan Pembelian Produk Kosmetik Wardah Pada Mahasiswi STIA Amuntai - Hasanah, Nurul; Azizah, Rismatul (Administraus, 2024)
ABSTRACT This research aims to determine the influence of brand image on the decision to purchase Wardah cosmetics among STIA Amuntai students. The majority of STIA Amuntai students use Wardah in their daily lives. This study applied quantitative methods, collecting data through questionnaires and documentation. The reasons consumers use Wardah cosmetic products are diverse, two of which are because they are cheap and suitable. Simple regression analysis and t-test are two data analysis techniques in this study. The results of this research study are as follows, in the simple linear regression analysis method with the equation Y = 4.888 + 0.712X which is further the simple regression coefficient of the Brand Image variable (X) worth 4.888, meaning that if the brand image variable is zero, the purchasing decision will increase by 4.888. Referring to the discussion of the study regarding the Effect of Brand Image on Wardah Cosmetic Purchasing Decisions on STIA Amuntai students. This means that if Wardah cosmetic products have a good brand image, it will increase strong purchasing decisions from consumers. This statement is proven through the t-test between the brand image variable on purchasing decisions with the acquisition of t count, namely 4.275> t table 1.679 and the significance value is 0.000 <0.05. Researchers hope Wardah can maintain its brand image and image as halal cosmetics. Keywords: Influence, Brand Image, Wardah